Exchange Rate and Macroeconomic Impacts on Indonesia’s Balance of Payments - Zahra, Zhafirah Kirana; Yuniarsih, Tia; Proboputri, Raisa Hasna Nabila; Maulana, Reksa Akbar; Nuaraya, Ahmad Setiawan (Santoso Academy Network, 2025)
Indonesia, as a nation that heavily relies on commodity exports, experiences notable impacts from exchange rate fluctuations in its efforts to maintain a stable balance of payments (BOP). This study seeks to analyze the influence of several macroeconomic variables specifically, the exchange rate, reference coal price (HBA), foreign exchange reserves, and gross domestic product (GDP) on Indonesia's balance of payments, particularly within the timeframe of 2013 to 2024. The research delves into the external economic vulnerabilities faced by Indonesia in light of global coal price dynamics and currency volatility. Utilizing a quantitative methodology, the study employs multiple linear regression analysis facilitated by EViews and Jamovi software, relying on time series data sourced from credible national and international sources. The findings indicate that, out of the four independent variables examined, only foreign exchange reserves demonstrate a statistically significant and positive impact on the balance of payments, underscoring their vital role in stabilizing the external sector. Conversely, the exchange rate, coal price, and GDP do not reveal significant individual effects. This research offers original insights into the stabilization of macroeconomic conditions in commodity-dependent economies and emphasizes the importance of strategic reserve management in mitigating balance of payments instability.